Normality in products of Rudin’s Dowker spaces which are constructed from Suslin trees - Kasai, Yosuke (Topology Proceedings, 2023)
If κ is the successor of an uncountable regular cardinal, N a finite integer and {R^i}_i N is a finite sequence of κ-Suslin trees such that _i N R^i has the κ-c.c., then _i N X^i is normal when X^i is a Rudin’s Dowker space that is constructed from R^i. Moreover, _i N X^i is again Dowker by the same assumption.